Elastic wave methods for non-destructive damage diagnosis in the axisymmetric viscoelastic cylindrical waveguide. (June 2021) - Jothi Saravanan, T.
Highlights: Numerical modeling of guided wave interaction with discontinuity is discussed. A 3D-hybrid method combining the classical FEM with a SAFE technique is implemented. Energy ratios are presented to study the interaction of guided waves with damages. Reflection and transmission coefficients for axisymmetric defects are estimated. A robust algorithm for elastic wave reflection and scattering is presented. Abstract: The popular technique for damage detection in a cylindrical waveguide is the ultrasonic guided wave propagation based acoustic emission (AE) monitoring method. It comes under the dynamic non-destructive evaluation (NDE) category, primarily established on the fluctuations in AE signal features to detect the structural damage in real-time. In this paper, the numerical modeling of wave scattering by a structural discontinuity in axisymmetric high strength steel wire - viscoelastic waveguide medium for analyzing the wave interaction by inhomogeneity is presented. The hybrid standard three-dimensional finite element (3D FE) method and semi-analytical finite element (SAFE) method for numerical analysis of guided ultrasonic wave propagation are employed. For the simulation of waveguide media with arbitrary defect shapes, the hybrid 3D FE-SAFE method can be used. The basic idea is to express the frequency response of the cross-section at the two ends of the 3D FE part as a modal superposition calculated by the semi-analytical method. A case study on a steel wire is conducted to calculate the displacement response under a narrow-band external force excitation. The AE signal characteristics are used to understand the wave interaction of the pitting corrosion and tapered section in steel wire. The investigation of the amplitude of elastic waves passing through the discontinuity for the both undamped and damped cylindrical waveguide is proposed to understand the distribution of energy at points of reflections or refraction and the ratio between the amplitudes arriving at that point. Another contribution of the research work includes the robust algorithm for wave reflection and scattering based on the hybrid element method, which can effectively improve the calculation competence using an internal degree of freedom condensation and modal acceleration. It is suitable for models with multiple damages in the 3D FE area, and the accuracy of the results on wave-damage interactions can be achieved. The recommended method can be used to distinguish damages present in a viscoelastic cylindrical waveguide.